Recent advances in micro-sized oxygen carriers inspired by red blood cells - Qiming Zhang; Natsuko F. Inagaki; Taichi Ito (Science and Technology of Advanced Materials)
Supplementing sufficient oxygen to cells is always challenging in biomedical engineering fields such as tissue engineering. Originating from the concept of a ‘blood substitute’, nano-sized artificial oxygen carriers (AOCs) have been studied for a long time for the optimization of the oxygen supplementation and improvement of hypoxia environments in vitro and in vivo. When circulating in our bodies, micro-sized human red blood cells (hRBCs) feature a high oxygen capacity, a unique biconcave shape, biomechanical and rheological properties, and low frictional surfaces, making them efficient natural oxygen carriers. Inspired by hRBCs, recent studies have focused on evolving different AOCs into microparticles more feasibly able to achieve desired architectures and morphologies and to obtain the corresponding advantages. Recent micro-sized AOCs have been developed into additional categories based on their principal oxygen-carrying or oxygen-releasing materials. Various biomaterials such as lipids, proteins, and polymers have also been used to prepare oxygen carriers owing to their rapid oxygen transfer, high oxygen capacity, excellent colloidal stability, biocompatibility, suitable biodegradability, and long storage. In this review, we concentrated on the fabrication techniques, applied biomaterials, and design considerations of micro-sized AOCs to illustrate the advances in their performances. We also compared certain recent micro-sized AOCs with hRBCs where applicable and appropriate. Furthermore, we discussed existing and potential applications of different types of micro-sized AOCs.